ANALISIS YURIDIS SOSIOLOGIS PENYIDIKAN TERHADAP TINDAK PIDANA PENCURIAN DENGAN PEMBERATAN DI POLSEK MOJOSONGO KABUPATEN BOYOLALI (PASAL 363 AYAT 1 KUHP) - WARSONO, JOKO (Dinamika Hukum, 2016)
Background research focus is motivated issue criminal offense of theft byweighting, by no means a problem that is simple, because sometimes officerscreated difficulties in uncovering a case and the perpetrators increasingly cleverfool officers in a way to cover his tracks as neat as possible, so the aboverationale, the writers take the title of “socio-juridical analysis of the investigationof the crime of theft by weighting in Mojosongo police station (article 363paragraph 1 of the criminal Code).The results are indicative of the crime of theft by weighting or livestocktheft committed by the suspect Arip Wulandoko bin Tukiman because it has beenthe fulfillment of the elements as defined in Article 363 paragraph (1) CriminalCode. Investigators at the time of assignment of the suspect Arip Wulandoko notknow the full name and residential address Eko brother and did not know in anymarket you shop EKO cows. When investigators searched and investigators arelooing for witnesses witness with regard to information no witnesses who sawwhen the suspect Arip Wulandoko meet by brother Eko other name JUNE soinvestigators difficulty in identifying the person named Eko and not knowingfellow employees or close friend of the brothers EKO JUNE other name so thisinvestigators and the investigators must coordinate all sat reskrim Boyolali. Sincefour cattle traders were photographed and shown to the suspect ARIPWULANDOKO and always refused fourth suspect named EKO photo, then itimpedes the process of gathering information from witnesses and evidence.Keywords : investigation, the crime of theft and weighting.